STRUCTURAL CHARACTERISTICS OF MESOPHASES AND MESOMORPHIC GLASSES OF METALALKANOATES - Gridyakina, Aleksandra; Polishchuk, Arkadiy (Proceedings of National Aviation University (archive), 2014)
The structure of the mesophases and mesomorphic glasses of cobalt alkanoates homologous series was obtained. It is shown, that typical for ITLC smectic A packing of molecules (cation-anion layer between layers alkanoate chains) preserves also in a glass phase (at room temperature).